High sensitivity cardiac troponin T in patients not having an acute coronary syndrome: results from the TRAPID-AMI study - Nowak, Richard M.; Giannitsis, Evangelos (Biomarkers, 2017)
To describe the baseline, 1 hr and delta high sensitivity cardiac troponin (hs-cTnT) values in patients with suspected acute myocardial infarction (AMI) but without a final acute coronary syndrome (ACS) diagnosis.
Gesehen am 20.08.2018